Uncommon Variant of Type II Monteggia Fracture with Concomitant Distal Humeral Fracture - Jihad F. Matta; George S. El Rassi; Hicham G. Abd El Nour; Rachel El Asmar (Case Reports in Orthopedics)
Monteggia fracture-dislocation, a common injury sustained by pediatric population, is a rare entity in adults. It was first observed by Giovanni Battista Monteggia and later classified by Bado into 4 groups. The term “Monteggia equivalent or variant” was introduced to describe certain injuries with similar radiographic pattern and biomechanism of injury. Since then various types and their variants have been described in the literature. We present a complex fracture pattern in a 55-year-old male not previously described in the literature along with its treatment modality and favorable outcome.